1998
DOI: 10.1021/ac9801667
|View full text |Cite
|
Sign up to set email alerts
|

Radial Flow Microring Electrode:  Development and Characterization

Abstract: The radial flow microring electrode (RFMRE), a new hydrodynamic ultramicroelectrode, is described. In the RFMRE, solution flows from a capillary nozzle, which is positioned very close to a planar substrate using micropositioners. The RFMRE can be operated in one of two configurations: either (a) with the ring electrode on the capillary or (b) with the ring electrode positioned in the plane of the substrate directly underneath the capillary. In both arrangements, as fluid leaves the capillary, it is forced into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 47 publications
4
53
0
2
Order By: Relevance
“…With conventional electrode systems under laminar flow conditions the maximum mass-transfer rates up to ca. 0.05 cm/s were reached, while with a radial flow microring electrode mass transfer coefficients in excess of 2 cm/s were reported [42]. Such systems are excellent tools for measurement of fast reaction rates [43].…”
Section: Flow Analysis With Voltammetric and Amperometric Detectionsmentioning
confidence: 95%
See 1 more Smart Citation
“…With conventional electrode systems under laminar flow conditions the maximum mass-transfer rates up to ca. 0.05 cm/s were reached, while with a radial flow microring electrode mass transfer coefficients in excess of 2 cm/s were reported [42]. Such systems are excellent tools for measurement of fast reaction rates [43].…”
Section: Flow Analysis With Voltammetric and Amperometric Detectionsmentioning
confidence: 95%
“…While in conventional-sized voltammetric systems with laminar flow a maximum mass-transfer rates up to about 0.05 cm/s is reached, for instance, in radial flow micro ring electrode (66 mm ring diameter) mass-transfer rates in excess of 2 cm/s can be achieved, which provides a significant enhancement of detection sensitivity [42]. A set of disk microelectrodes of radii ranging from 5 to 25 mm was used in a wall-jet cell with amperometric detection for indirect determination of nitrite in saliva based on its reaction with iodide [122].…”
Section: Miniaturization In Flow Electroanalysismentioning
confidence: 99%
“…Thus the key issue of achieving an effective mass transfer rate, (∼D/d) higher than heterogeneous kinetics, could be greatly affected due to the tip size. This problem could be minimized by using the impinging jet 29,30 since such hydrodynamic approaches produce significantly high mass transfer rates, studies in this regard are now underway in our group. A high rate constant value for H2 oxidation at 0.2 -0.5 µm Pt particles was also noticed earlier.…”
Section: H2 Oxidation On Pt-pani-hopg: Heterogeneous Et Kineticsmentioning
confidence: 99%
“…9 Taking an advantage of the very small tip size, pulled glass capillaries have been employed as microholders for constructing electrochemical microsensors, such as carbon fiber microelectrodes, 10,11 bilayer lipid membrane microsensors [12][13][14] and oxygen microsensors, 15 and also in achieving enhanced and variable mass-transfer rates at a hydrodynamic ultramicroelectrode. 16 The use of glass capillaries with a conical or cylindrical tip (1.5 -2 µm) as a diffusional microburet for microtitration [17][18][19] and quantitative reagent delivery for fine chemical manipulations 20,21 has also been reported. Recently, Wei et al have reported that pulled quartz tubes with orifice radii of ~20 nm form a diffuse electrical double layer within the tip, leading to charge-selective ion movement across the tip.…”
Section: (Received August 3 2000; Accepted September 6 2000)mentioning
confidence: 99%